Algorithms for drawing polyhedra from 3-connected planar graphs - Orbanić, Alen (Informatica (Ljubljana), 2004)
Two algorithms for producing polyhedral representations for 3-connected planar graphs are discussed in the paper. One of them uses Tutte's drawing algorithm to produce 2D drawing. Then the drawing is lifted into 3D space obtaining a polyhedral embedding. The other is simple algorithm by G. Hart for drawing canonical polyhedral representations. Some alternative aspects (physical model, Markov chain model) in algorithms for obtaining Tutte's drawings are presented and proved.
Keywords: teorija grafov; prikaz podatkov; vizualizacija